Studi Komparatif Metode Perkuatan Struktur Beton Bertulang Berdasarkan Tinjauan Literatur, Pengujian Balok, dan Rehabilitasi Pascabencana - Anwar; Dian Nanda Islami; Muhammad Rifal Fan Putra (Dept. of Civil Engineering Universitas Riau, 2024)
Retrofitting is a key strategy to restore or enhance the performance of reinforced concrete structures damaged by overloading, deterioration, fire, or seismic events. This study synthesizes findings from three approaches: a literature review, experimental testing using FRP on reinforced beams, and a case study involving post-fire strengthening with CFRP and steel bracing. Various methods epoxy injection, concrete jacketing, FRP, CFRP, and bracing are compared based on effectiveness, structural impact, and application context. Results indicate that CFRP and FRP significantly improve flexural and shear strength, epoxy injection is suitable for minor cracks, and concrete jacketing enhances capacity substantially. For fire-damaged structures, combining CFRP and steel bracing effectively reduced drift ratios and restored structural integrity. SAP2000 modeling results align closely with experimental data, confirming its reliability in retrofit analysis. The study highlights that retrofit selection must consider damage level, element type, and cost-efficiency.